THE IMPORTANCE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING MORAL EDUCATION SUBJECTS - Xatamova Ma’rifat Yorkinovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This article examines the role and effectiveness of modern pedagogical technologies in teaching moral education (tarbiya) subjects within contemporary educational environments. As global education systems increasingly adopt learner-centered approaches, the integration of digital tools and innovative teaching strategies has become essential. This study applies a mixed methods design to evaluate how such technologies influence student engagement, academic performance, and moral value formation. The findings demonstrate that technology-enhanced instruction significantly improves students’ motivation, participation, and ability to apply ethical concepts in real-life situations. The article concludes that modern pedagogical technologies, when applied systematically and purposefully, play a crucial role in improving the quality of moral education.